Examining Tafsir Nurul Bajan by Moh. Romli and N.H.S. Midjaja: A Nusantara Tafsir Study in Sundanese - Fadhlurrahman, Zulfi; Anwar, Zaeni (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2025)
The interpretation of the Qur'an in local languages is an effort to make Islamic teachings more easily understood by local communities. This study examines Tafsir Nurul Bajan by Moh. Romli and N.H.S. Midjaja, a Qur'anic exegesis written in the Sundanese language. The research aims to analyze its content, method of interpretation, and the Islamic values it contains, particularly within the Sundanese cultural context. Through a literature review, the study finds that this tafsir uses simple and easily understandable Sundanese. Its interpretation emphasizes ethics, sharia, Sufism, and moral messages relevant to daily life. The author also utilizes Sundanese proverbs and expressions to clarify the meaning of the verses. It is concluded that Tafsir Nurul Bajan is a significant example of local tafsir, demonstrating the vital role of Nusantara scholars in conveying Islamic teachings in a contextualized and grounded manner to their local communities.